2022
DOI: 10.1002/adfm.202206845
|View full text |Cite
|
Sign up to set email alerts
|

Enabling Conversion‐Type Iron Fluoride Cathode by Halide‐Based Solid Electrolyte

Abstract: The practical application of low‐cost and energy‐dense iron fluoride cathodes is hindered by the first cycle electrochemical irreversibility, cycling instability, and large voltage hysteresis. Here, it is reported that these challenges may be overcome by the utilization of halide‐based solid electrolytes (SEs). The excellent electrochemical stability of halide‐based SEs enables a complete conversion and deconversion of FeF2 that cannot be achieved with sulfide‐based SEs. Due to restricted and reversible decomp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 76 publications
1
9
0
Order By: Relevance
“…It was also reported that halide‐based SEs enable matching with conversion cathodes, such as FeF 2 . [ 99 ] Recently, Han et al reported that the FeF 2 cathode demonstrates superior electrochemical performance in the Li 3 YCl 6 ‐based system, compared with the conventional liquid electrolyte system. This effect is ascribed to the restricted and reversible decomposition of Li 3 YCl 6 SEs, prevention of transition‐metal dissolution, mechanical confinement of active materials, and improved kinetics.…”
Section: Interfaces In Halide‐based Lmsbsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was also reported that halide‐based SEs enable matching with conversion cathodes, such as FeF 2 . [ 99 ] Recently, Han et al reported that the FeF 2 cathode demonstrates superior electrochemical performance in the Li 3 YCl 6 ‐based system, compared with the conventional liquid electrolyte system. This effect is ascribed to the restricted and reversible decomposition of Li 3 YCl 6 SEs, prevention of transition‐metal dissolution, mechanical confinement of active materials, and improved kinetics.…”
Section: Interfaces In Halide‐based Lmsbsmentioning
confidence: 99%
“…Besides, they highlighted the significant effect of SE composition on the redox behavior of the FeF 2 cathode, and Li 3 YCl 6 is demonstrated to enable a complete conversion and reconversion of FeF 2 that cannot be achieved with sulfide‐based 75Li 2 S‐25P 2 S 5 SEs. [ 99 ]…”
Section: Interfaces In Halide‐based Lmsbsmentioning
confidence: 99%
“…The confinement and compaction of the multi‐phase reaction products by the garnet electrolyte enable a high‐rate performance (330 mAh g −1 even at 2 C). Moreover, the remarkable electrochemical stability of the halide‐based solid‐state electrolyte allows for the complete conversion of FeF 2 cathode [133] . It is shown that the same concept employing halide‐based solid‐state electrolytes can be extended to other conversion cathodes to overcome the challenges inherent in metal fluorides.…”
Section: Strategies Of Improved Fefx Performancementioning
confidence: 99%
“…Moreover, the remarkable electrochemical stability of the halide-based solid-state electrolyte allows for the complete conversion of FeF 2 cathode. [133] It is shown that the same concept employing halide-based solid-state electrolytes can be extended to other conversion cathodes to overcome the challenges inherent in metal fluorides.…”
Section: Electrolyte Engineeringmentioning
confidence: 99%
“…[26] While SSBs based on LiPON thin-film electrolyte have been demonstrated to have a calendar life of >10 years, [27] we propose that long calendar life cannot be assumed for bulk-type SSBs based on sulfide, Li-garnet oxide, and halide SEs due to the drastically different electronic conductivity of SEs (the electronic conductivity of LiPON is 10 −14 to 10 −13 S cm −1 ). [27][28][29][30] Whether the electronic conductivity of the bulk-type SEs is sufficiently low to enable a long calendar life remains unknown for the SSB community. If we do a similar rough estimate for a future 4 V SSB with a 5 mAh cm −2 areal capacity and a 30-µm-thick SE using Ohm's law, the electronic conductivity of the SE should be lower than 5.7×10 −12 S cm −1 to enable a long calendar life of 15 years.…”
Section: Introductionmentioning
confidence: 99%